Transsynaptic inhibition of spinal transmission by A2 botulinum toxin. (18th December 2012) - Akaike, Norio; Shin, Min‐Chul; Wakita, Masahito; Torii, Yasushi; Harakawa, Tetsuhiro; Ginnaga, Akihiro; Kato, Keiko; Kaji, Ryuji; Kozaki, Shunji
Key points: Botulinum toxin A (BoNT/A) blocks synaptic transmission via the cleavage of SNAP‐25. Axonal transport of BoNT/A (A1 type botulinum toxin (A1LL) and A2 type botulinum toxin (A2NTX)) from periphery to the CNS has been described in trigeminal nerve and foreleg muscles. A1LL and A2NTX were injected into the ipsilateral soleus, and their effects on ipsilateral and contralateral contractions were compared as a measure of local and systemic/transport‐mediated effects. Spinal transmission was also measured to determine axonal and transsynaptic transport of neurotoxin. A2NTX induced faster and stronger muscle relaxation than A1LL. A1LL arrived at the contralateral muscle by almost equal transport via neural pathways and by the circulation. A2NTX was mainly transported to contralateral muscles via the blood. A1LL and A2NTX were carried from peripheral to CNS and vice versa by dual antero‐ and retrograde axonal transport through either motor or sensory neurons. Our results may point to greater potential safety in A2NTX form. Abstract  Type A botulinum toxin blocks not only ACh release from motor nerve terminals but also central synaptic transmission, including glutamate, noradrenaline, dopamine, ATP, GABA and glycine. Neurotoxins (NTXs) are transported by both antero‐ and retrogradely along either motor or sensory axons for bidirectional delivery between peripheral tissues or the CNS. A newly developed type A2 NTX (A2NTX) injected into one rat foreleg muscle was transported to the contralateral muscle. This finding was consistent with the NTX traveling retrogradely via spinal neurons and then transsynaptically through motor neurons to the contralateral motor neurons within the spinal cord and on to the soleus muscle. In the present study we found that toxin injection into the rat left soleus muscle clearly induced bilateral muscle relaxation in a dose‐dependent fashion, although the contralateral muscle relaxation followed the complete inhibition of toxin‐injected ipsilateral muscles. The toxin‐injected ipsilateral muscle relaxation was faster and stronger in A2NTX‐treated rats than A1LL (BOTOX). A1LL was transported almost equally to the contralateral muscle via neural pathways and the bloodstream. In contrast, A2NTX was mainly transported to contralateral muscles via the blood. A1LL was more successfully transported to contralateral spinal neurons than A2NTX. We also demonstrated that A1LL and A2NTX were carried from peripheral to CNS and vice versa by dual antero‐ and retrograde axonal transport through either motor or sensory neurons.